Mechanical Properties Analysis of Medium Carbon Steel Heated at 850°C by Quenching in NaOH Solution - Sitorus, Stefen; Sinuhaji, Perdinan (Journal of Technomaterial Physics, 2021)
The aim of this study is to analyze the mechanical properties of carbon steel medium by quenching in NaOH solution. Heating medium of the carbon steel in a heating furnace is 850°C. The cooling process in NaOH solution was varied in concentration of NaOH (5%, 10%, 15%, 20%, 25%), and the sample was allowed to reach room temperature (27°C). The original medium carbon steel hardness value is 9.4 HRC and the tensile strength value is 656.85 MPa, while for materials with heat treatment processes and cooling processes with different concentrations of NaOH (5%, 10%, 15%, 20%, 25%) resulted in hardness values of 57 HRC, 58.3 HRC, 58.5 HRC, 60 HRC, 57.5 HRC and tensile strength values of 728.50 MPa, 835.99 MPa, 987.26 MPa, 1035 MPa, and 855 MPa for different concentrations of NaOH (5%, 10%, 15%, 20% , 25 %). Analysis of XRD crystalline structure on medium carbon steel with intermediate carbon steel from the three highest peaks of each test sample was found that its orthorhombic crystal structure in which lattice parameters a, b, and c.